Tax Literacy: Tax Knowledge For Students Yppgi Sentani Junior High School Jayapura Regency - Meinarni Asnawi; Pascalina V.S Sesa (International Journal Of Community Service, 2024)
Tax is the implementation of obligations that are paid voluntarily. This understanding needs to be done from the beginning to the younger generation to increase tax awareness because it is an important point considering that taxes are one of the sources of state revenue that will be used for development. Introducing taxes and various benefits of tax reporting is important for students to prepare themselves as mandatory subjects and will subsequently become taxpayers. This community service aims to increase tax understanding from an early age through the provision of tax knowledge for students of YPPGI Junior High School,  Jayapura Regency. Tax material is focused on three things: the definition of taxes and tax benefits, sources of state revenue, and the importance of paying taxes. Tax literacy teaches students the obligations, and procedures of being a taxpayer. Participants in this activity are 58 YPPGI students in Grades 7 and 8, it is hoped that the students can understand the importance of taxes as one of the sources of state revenue and realize their tax obligations from an early age—teaching methods through lectures, tax video screenings, and games. Learning activities results showed a positive difference in tax knowledge before and after the material was given. Students are happy with the material taught and aware of the tax obligations if they work later.